2016
DOI: 10.1007/s00193-016-0676-6
|View full text |Cite
|
Sign up to set email alerts
|

On the propagation mechanism of a detonation wave in a round tube with orifice plates

Abstract: This study deals with the investigation of the detonation propagation mechanism in a circular tube with orifice plates. Experiments were performed with hydrogen air in a 10-cm-inner-diameter tube with the second half of the tube filled with equally spaced orifice plates. A self-sustained Chapman-Jouguet (CJ) detonation wave was initiated in the smooth first half of the tube and transmitted into the orifice-plate-laden second half of the tube. The details of the propagation were obtained using the soot-foil tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…The simulations showed that hot spots are generated in obstructed tubes (both straight and bent), which is in accordance with the works reported in Ref. 59,62. More recently, Li et al [48] conducted experiments to study the incident waves for DDT in ethylene-air mixtures in an S-shaped tube.…”
Section: Flame Acceleration Ddtsupporting
confidence: 86%
See 1 more Smart Citation
“…The simulations showed that hot spots are generated in obstructed tubes (both straight and bent), which is in accordance with the works reported in Ref. 59,62. More recently, Li et al [48] conducted experiments to study the incident waves for DDT in ethylene-air mixtures in an S-shaped tube.…”
Section: Flame Acceleration Ddtsupporting
confidence: 86%
“…Experimental, theoretical, and numerical studies focused on flame acceleration and DDT in smooth tubes and obstructed tubes have been performed in some previous literature [51,[53][54][55][56][57][58][59]63]. As suggested by Silvestrini et al [53], the relation between the flame velocity and position in smooth tubes follows an exponent function:…”
Section: Flame Acceleration Ddtmentioning
confidence: 99%
“…In this study, experiments were performed in a tube filled with orifice plates to obtain the DDT composition limit of ethanol-air mixtures. The tests were carried out in the same 10-cm diameter tube and 0.44 BR orifice plates used in the Ciccarelli and Cross (2016) experiment that confirmed the applicability of the DDT criterion d/λ = 1 for gaseous fuels. Using the DDT composition limits measured in this study for ethanol-air, and the DDT criterion of d/λ = 1, it is possible to determine which cell size data reported by Diakow et al (2015), i.e., small or large, should be used to predict DDT for ethanol-air mixtures.…”
Section: Introductionmentioning
confidence: 79%
“…Detonation initiation typically occurs as the result of the interaction of the lead shock wave with the obstacle face, or the tube wall (Rainsford and Ciccarelli, 2017). Ciccarelli and Cross (2016) studied the influence of the orifice blockage ratio (BR) on the DDT limit (i.e., minimum mixture composition resulting in DDT). The BR is defined as the ratio between the cross-sectional area of the tube blocked by the obstacle and the cross-sectional area of the tube; for a tube with diameter D, the BR is BR ¼ 1 À d=D ð Þ 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In this set-up, detonation propagation has been primarily classified according to average combustion front velocity derived from time-of-arrival measurements taken at regular intervals along the combustion channel [5]. More recently, sooted foils, which provide information on detonation structure, have been used inside the combustion channel between obstacles to better understand detonation propagation [6].…”
Section: List Ofmentioning
confidence: 99%